Topsy and Tim have a birthday party - Adamson;Jean (London Ladybird, 1995)
"Topsy and Tim are always finding fun adventures in the real world, and this story is reassuring for young children having first experiences of their own. It's Topsy and Tim's birthday and that means a party! Follow their adventures as they hang the decorations, open their presents and share the fun with all their friends"